Coat Protein Gene: A key tool for Yam Mild Mosaic Virus diagnosis in greater yam - M.L. Jeeva; T. Makeshkumar; Tom Cyriac; P.R. Amrutha; S.U. Shilpa; M. Rajitha (JOURNAL OF ROOT CROPS, 2024)
Destruction of infected plants and use of virus-free planting materials are the common control measures used for preventing viral infections. These practices are inadequate to combat the virus attack in many incidents. Early detection of infection is an effective way to manage the systemic primary spread of viruses. Infection caused by Yam mild mosaic virus (YMMV), one of the major viruses in yams (Dioscorea spp) is difficult to detect in the early stages. Symptoms include mild mosaic, leaf mottling, and chlorosis and leaf distortion. In the present study, PCR was employed for the amplification of YMMV coat protein (CP) gene for diagnosing the virus from greater yam (Dioscorea alata L.) leaves. The specific primer pair was designed and validated for CP gene amplification, which yielded an amplicon of 810 bp in YMMV positive samples. Subsequent cloning in pUC18 vector and sequencing confirmed the presence of the full coat protein (CP). In addition to PCR-based diagnostic method, the accomplished isolation and characterization process opens avenues for generating virus-specific polyclonal antibodies through the utilization of the expressed coat protein. These antibodies can be further employed in serological techniques.